Corporate governance and ownership structure on illegal insider trading activities in Malaysian public listed companies / Suhaily Hasnan ...[et al.] - Hasnan, Suhaily; A. Rahman, Nor Azlina; Mohamed Hussain, Alfiatul Rohmah; Mohd Ali, Mazurina (Universiti Teknologi MARA, 2022)
This study examined the effect of corporate governance and ownership structure on illegal insider trading activities in public listed companies in Malaysia. Specifically, this study examined the effect of board independence, audit quality, family ownership, managerial ownership and institutional ownership on illegal insider trading activities in public listed companies in Malaysia. This study used content analysis on the annual reports over a 16-year period from 2000 to 2015 of 112 Malaysian public listed companies. Out of the 112 public listed companies, 22 public listed companies were involved in illegal insider trading activities, whilst the remaining 90 were not. This study showed that audit quality and managerial ownership significantly influence illegal insider trading activities, whilst board independence, family ownership and institutional ownership do not have a significant influence on illegal insider trading activities in public listed companies in Malaysia. These findings may assist the relevant authorities in strengthening enforcement to minimize illegal trading activities in the Malaysian securities market.